(untitled) (Third Sector Social Economic Review, 2018)
The advantages of social media over traditional communication tools have attracted the attention of public institutions, particularly that of brands and companies, and ultimately that of civil society organizations, and numerous non-governmental organizations (NGO) have begun to use this medium. Social media, which enables NGOs to reach a wider audience, interact with their followers, react promptly to sudden changes, etc., is, unfortunately, not used by most NGOs effectively enough. In this study, social media activities of two major NGOs, Turkish Red Crescent and Turkish Green Crescent, which operate in Turkey are evaluated in the light of the findings of semi-structured interviews conducted with corporate communications executives of these two NGOs. According to the findings, it is concluded that both NGOs use more than one social media channel actively.